A review on microwave band pass filters: Materials and design optimization techniques for wireless communication systems. (February 2023) - Krishna V, Neeraj; Padmasine, K.G.
Abstract: Microwave band pass filters play an important function in radio frequency for suppressing out-of-band emissions that are necessary in today's wireless communication. The study discusses the various materials and techniques used in the creation of microwave band pass filters. Different resonator designs, defective ground structure methodologies, and types of dielectric materials utilised for design are all explored. Microwave band pass filters used in wireless communication systems at various frequency bands have major features to manage frequency response in the pass and stop bands. The best performance of microwave band pass filters is estimated using optimization approaches to ensure crisp transitions at cut-off frequencies, compactness, high selectivity, low insertion loss, greater fractional bandwidth, and high return loss. The research shows that choosing the right fabrication techniques and materials improves the performance of microwave band pass filter designs, making them more practical for developing wireless communication systems.